A Comparative Study Of Some Physical Attributes Among Different Playing Positions Of Football Players - Salah Mohammed Shaddoud (Musamus Journal of Physical Education and Sport (MJPES), 2026)
Football is a diverse game that requires players to have multiple physical abilities, physical characteristics, and skills that are closely linked to each other to achieve excellence. The preparation of players and the improvement of their technical, physical, and tactical-psychological levels are the primary goals for which training programs are built and tests are conducted. However, the question remains as to which physical attribute is more available than others for this success. Therefore, the choice was made to focus on two important physical attributes in the game, namely speed-strength and agility. The importance of the research lies in revealing which of the different playing positions in football possess one of these two attributes more than others. The problem of the research is that the researcher observed through his field experience that all team players are subjected to the same physical exercises without distinguishing between one position and another in football. Since each playing position has specific characteristics and physical attributes to a certain degree that players must possess, the problem of the research lies in determining which of the different playing positions in football requires speed-strength and agility more than others.The objectives of the research are to identify the level of speed-strength among Al-Nasiriya Club football players, to identify the level of agility among Al-Nasiriya Club football players, to identify the differences between different playing positions in football in terms of speed-strength among Al-Nasiriya Club football players, and to identify the differences between different playing positions in terms of agility among Al-Nasiriya Club football players. The researcher used the descriptive approach, which is suitable for the nature of the research problem. The sample was chosen intentionally from Al-Nasiriya Club football players. The researcher used a set of necessary devices and tools to help obtain the required results to achieve the objectives and hypotheses of the research, in addition to relying on appropriate statistical means to process the results obtained.